The role of German universities in a system of joint knowledge generation and innovation. A social network analysis of publications and patents with a focus on the spatial dimension - Meyborg, Mirja (KIT Scientific Publishing, 2013)
There is broad consensus that universities play a key role as knowledge platform in regional economic development. This book exactly picks up this line of thought and explores the role of the German universities in a system of joint knowledge generation and innovation. The overall aim of this book is to provide new insight into the German universities’ behavioural patterns regarding their knowledge generation, innovation and collaboration function.